(untitled) (The Review of Diabetic Studies, 2025)
Objective: To estimate the correlation between C-reactive protein (CRP) and Carcinoembryonic Antigen (CEA) in obese adults in Cartavio, Ascope province, Peru, in 2024. Material and Methods: This was a correlational, cross-sectional study. One hundred thirty-seven residents between 40 and 80 years old with obesity (BMI ≥30 kg/m2) participated. Anthropometric assessment was used to calculate the BMI value, and a biochemical analysis of blood serum was performed to determine CRP and CEA levels. Results: Both markers had elevated values: CRP 95% CI: 32.6–68.0 mg/L and CEA 95% CI: 39.9–159.9 ng/mL. Additionally, a high positive correlation (ρ=0.841) was determined between C-reactive protein and Carcinoembryonic Antigen. Conclusion: There is a ** strong correlation between CRP and CEA** in obese adults from the small town of Cartavio in the province of Ascope, Peru, 2024.